Writing Strategy Use: AFL Learners in Sri Lanka - Gafoordeen, N. (Maxwell Scientific Organization, 2014)
Study on writing strategy used in Arabic as a foreign language is a new emerging concept. Few studies have contracted on essay written in Arabic as a final product and illustrated deficiencies that surfaced. This study investigates the writing strategies employed by 6 learners in Fathih Institute of Sri Lanka (FISL). A Qualitative research was conducted using the think aloud protocol; observation and retrospective interview to provide the facts. Results of a pilot study revealed that a proficient learner employ varieties of writing strategies better than an average learner and less proficient learners on their essay writing tasks. The findings also revealed that there is a lot to be done to improve the Arabic writing skills of Sri Lankan learners. The implications of the results are that, teachers need to rethink about the problems that average and less proficient students encounter and figure out ways to help them achieve proficiency. Also, there is the need to help these learners how to make their place and organize their opinions more reasonably in writing activities.
Keywords: Writing Strategy Use: AFL Learners in Sri Lanka